Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2004
DOI: 10.1145/985692.985756
|View full text |Cite
|
Sign up to set email alerts
|

Revealing delay in collaborative environments

Abstract: Delay is an unavoidable reality in collaborative environments. We propose an approach to dealing with delay in which 'decorators' are introduced into the interface. Decorators show the presence, magnitude and effects of delay so that participants can better understand its consequences and adopt their own natural coping strategies. Two experiments with different decorators show that this approach can significantly reduce errors in specific collaborative activities. We conclude that revealing delays is one way i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…Although Time Warp has been recommended for fast-paced games [5], the use of rollback can be distracting and confusing; locations of shared objects change suddenly, and users experience gaps in the ordering of events [10].…”
Section: Hiding Delaymentioning
confidence: 99%
See 2 more Smart Citations
“…Although Time Warp has been recommended for fast-paced games [5], the use of rollback can be distracting and confusing; locations of shared objects change suddenly, and users experience gaps in the ordering of events [10].…”
Section: Hiding Delaymentioning
confidence: 99%
“…These are now common in many games, where information such as ping times show the delay for individual clients. Studies have shown that users are able to perform better when they are more informed in this way [7,10]. Decorators are an extension of this idea, and place indications in the game environment itself [22].…”
Section: Revealing Delaymentioning
confidence: 99%
See 1 more Smart Citation
“…However, similar to game-like tasks (e.g., [5]), the effect of delay on document editing, as measured by outcome, depends on strategy. A tightly coupled subtask decomposition that enhances outcome in the presence of minimal delay becomes detrimental at higher levels of delay, potentially less effective than a more loosely coupled task decomposition at the beginning of the task.…”
Section: Discussionmentioning
confidence: 99%
“…Both the avoidance and resolution of such interactions requires communication among the team members [4]. However, not all tasks are sensitive to delay [2] and users might pursue strategies that are not sensitive to delay, or they might adjust their strategies if they are aware of delay [5].…”
Section: Introductionmentioning
confidence: 99%